Conference "Professional and corporate ethics in the modern stage of socio-humanitarian knowledge" - M. M. Rohozha, (Ukrainian Cultural Studies, 2019)
On November 23-24, 2017, a scientific and practical conference (with international participation) "Professional and corporate ethics at the modern stage of socio-humanitarian knowledge" was held on the basis of the Department of Ethics, Aesthetics and Cultural Studies of Taras Shevchenko Kyiv National University, at which the intermediate results of the work were presented on the scientific research of the department "Professional and corporate ethics: problems of substantiation and implementation".